Pressure drop analysis in a pin type mini channel / Nurul Izzati Azmi … [et al.] - Azmi, Nurul Izzati; Wan Dagang, Wan Nur Fatini Syahirah; Muhammad Arif, Hazwani Izzati; Sainan, Khairul Imran (Universiti Teknologi MARA, 2021)
The mini channel is used widely in industrial applications. The application includes a heat exchanger device, as a part of a cooling system or as a reactant transport channel. However, unlike the pressure drop determination of a piping network, where the loss coefficient values for the bends and fittings are available, similar cannot be done for the mini channel. The loss coefficient values for the channel are rarely determined and reported. The aim of this study is to propose a correlation for the prediction of total pressure drop in a mini channel resulting from the loss coefficient. The results were compared against a numerical simulation. A 42 mm x 50 mm pin type mini channel was used as the sample of the study. The fluid was hydrogen. The flow regime was kept as laminar. The numerical simulation was performed on the whole active area. The correlation was calculated using the loss coefficient values of bends that were determined beforehand. Three correlations were proposed. Statistical values were used as the comparison parameters. Based on the results, an almost similar pressure drop was predicted by correlation III (diff. mean ± SD = 0.005 ± 0.006 kPa). The correlation I and correlation II were not able to predict the expected results at all. The results were from a low Reynolds (range of Re < 200) number. In general, the correlation proposed successfully predicted the pressure drop in a pin-type mini channel using the loss coefficient value of the individual bends.